Music therapy in education - Lavska, V. (ХНУ ім. В. Н. Каразіна, 2012)
The article deals with the use of music therapy in the field of education. Different aspects of music are analyzed. Some advantages and disadvantages of music therapy are considered. Special attention is paid to the use of music therapy in the Zaporozhye State University. The conclusion is made that that there is no adequate training in Ukraine regarding the educational needs of students with disabilities and limited knowledge of effective teaching strategies to meet those needs.
Статья посвящена использованию музыкотерапии в области образования. Анализируются различные аспекты музыкальной терапии. Рассматриваются недостатки и преимущества музыкотерапии. Особое внимание приселяется использованию музыкотерапии в запорожском государственном университете. Выводом этого является то, что на сегодня в Украине отсутствует необходимая профессиональная подготовка для преподавателей, чтобы использовать методы преподавания для удовлетворения потребностей учащихся и студентов с ограниченными возможностями.
Keywords: brainwaves; health; university; music